16.9 MW, efficient 486.1 nm blue optical parametric oscillator using single BBO crystal. (7th January 2021) - Zhang, Jiale; Ma, Jian; Lu, Tingting; Wang, Jianlei; Zhu, Xiaolei; Chen, Weibiao
Abstract: A single-resonant beta barium borate crystal optical parametric oscillator with high pulse energy output at the H-β Fraunhofer line of 486.1 nm was demonstrated. Pumped by a single-frequency 355 nm ultraviolet pulsed laser at 10 Hz repetition rate with maximum pulse energy of 411 mJ, maximum output energy of 162 mJ blue laser pulse at 486.1 nm was successfully obtained from a plano-concave cavity with a 40% output coupler, the corresponding optical-to-optical conversion efficiency was up to 39.4%, and the pulse width was around 9.6 ns. The blue laser beam size was 4.4 mm × 5.1 mm with the beam divergence angles of θx = 2.2 mrad and θy = 2.5 mrad. The peak power of output blue laser was 16.9 MW, and the signal linewidth was around 0.34 nm.